The common law choice of law rules for resulting and constructive trusts - CHONG, Adeline (Institutional Knowledge at Singapore Management University, 2005)
There is a dearth of authority and in-depth discussion concerning what the choice of law rules are for claims involving the assertion that property is held on a resulting or constructive trust. It is usually thought that the choice of law rules set out by the Hague Convention on the Law Applicable to Trusts and on their Recognition (hereafter the ‘Hague Trusts Convention’), as enacted into English law by the Recognition of Trusts Act 1987, apply. However, it is arguable that this is not so for some types of resulting and constructive trusts, namely those governed by a foreign law; or, at the very least, that some doubt exists as to whether the Hague choice of lawrules apply to all resulting and constructive trusts. It is therefore important that the common law choice of law rules for such trusts is clearly elucidated. Unfortunately, this is an area of the law that is distinctly undeveloped. The aim of this article is to consider what are or should be the common law choice of law rules for resulting and constructive trusts.